Perceived Value dan Loyalitas Pengguna Kartu Kredit: Peran Kepuasan Sebagai Variabel Pemediasi - Dhian Wahyuni; Ihsanuddin Ihsanuddin (Universitas Batanghari, 2019)
The research study aims to investigate the effect of perceived value on customer satisfaction and its impact on the behavioral loyalty of commercial bank credit card users in Banda Aceh. The research sample are 132 credit card users taken by random sampling. Data collection uses a questionnaire, and then the data is analyzed by statistical means of structural equation model (SEM) AMOS 21. The study found that perceived value has a positive and significant effect on satisfaction and loyalty of commercial bank credit card users. The satisfaction also has a positive and significant effect on loyalty of credit card users. The existence of satisfaction strengthens the influence of perceived value on loyalty of credit card users. The mediating effect of satisfaction as an intervening variable between the perceived value and loyalty is partial mediation.